Risk assessment of nanofertilizers - Viçozzi, Gabriel Pedroso; Pascoli, Mônica [UNESP]; Pilissão, Luiz Eduardo Ben; Barbosa, Matheus Teixeira; Ávila, Daiana Silva (Elsevier, 2024)
Nanofertilizers have revolutionized agriculture due to an increase in crop productivity. Some features comprise the control of the release of the nutrients, reduced degradation, and improved and targeted delivery, which reduce the need for excessive amounts of products to be applied. However, most of these products have an unknown effect on soil, the microbiota, and humans. Of note, these products contain metals or metal oxide, which can bioaccumulate and cause damage to several species, impacting the environment. Hence, risk assessments need to be performed for each new product, as well as surveillance in the workspaces and biomonitoring in the soil and water near crops. This book chapter will address risk assessment approaches for nanofertilizers and highlight some outcomes regarding studies on their ecological impacts using nontarget organisms, particularly those that live in soil and aquatic systems.
Keywords: Agrochemicals; Ecotoxicity; Fate studies; Nanomaterials; Nontarget organisms